The Predictive Model of Hope Based on Attachment Styles and Time Perspective with the Mediation of Self-Esteem in Students - Zohori Zangeneh, Zohreh; Emamipour, Susan; Baghdasarians, Anita (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The present study aimed to provide a predictive model of hope based on attachment styles and time perspective with the mediation of self-esteem in students. Methods and Materials: The research method was descriptive-correlational and path analysis. The statistical population of this study included all undergraduate students of non-governmental universities in Tehran, who were studying in the academic year 2019-2020. The statistical sample included 480 students selected using the cluster random sampling method. The tools used included the Attachment Style Questionnaire (ASQ) (Hazan & Shaver, 1987); the Time Perspective Questionnaire (TPQ) (Zimbardo & Boyd, 1999); the Self-Esteem Questionnaire (SEQ) (Rosenberg, 1979), and the Hope Questionnaire (HQ) (Simpson, 1999). Data analysis was performed using path analysis with SPSS and AMOS software version 23. Findings: The results showed that secure, avoidant, and ambivalent attachment styles, time perspective, and self-esteem have a significant correlation with hope in students (p < .01). Also, secure, avoidant, and ambivalent attachment styles, time perspective, and self-esteem have a significant direct effect on students’ hope (p < .01). Additionally, bootstrap results indicated that self-esteem has a significant mediating role in the relationship between attachment styles and time perspective with students’ hope (p < .01). Finally, the model had a good fit. Conclusion: Considering the significant mediating role of self-esteem, it is necessary for therapists and counselors to use appropriate psychological training to increase self-esteem in students, thereby improving their hope.